2002
DOI: 10.5650/jos.51.669
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementation of a Reductone in Coffee, Hydroxyhydroquinone, on Lipid Peroxidation and DNA Damage of Rat Organs.

Abstract: The present study was undertaken in order to know the effect of supplementation of a reductone in coffee, hydroxyhydroquinone (HHQ), on lipid peroxidation and DNA damage of rat organs. Wistar male rats were fed a diet containing HHQ at 2.0% (w/w) for 1 wk. The extents of lipid peroxidation of lung and heart were increased by HHQ supplementation but that of liver was not, when assessed by the levels of phospholipid hydroperoxides and thiobarbituric acid-reactive substances. In contrast, the extents of DNA damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…It was reported that the oral administration of HHQ to rats enhanced lipid peroxidation in the lungs and heart but did not enhance DNA damage as indexed by 8-hydroxy-2 ′deoxyguanosine [11]. However, we hypothesized that the effects of HHQ may be detectable in SAMP8 mice, which are more sensitive to oxidative injury.…”
Section: Introductionmentioning
confidence: 82%
“…It was reported that the oral administration of HHQ to rats enhanced lipid peroxidation in the lungs and heart but did not enhance DNA damage as indexed by 8-hydroxy-2 ′deoxyguanosine [11]. However, we hypothesized that the effects of HHQ may be detectable in SAMP8 mice, which are more sensitive to oxidative injury.…”
Section: Introductionmentioning
confidence: 82%